Use of hydraulic simulation as a tool in decision making in water supply network: a case study in the Brazilian city of São Gabriel, RS - Martins, Matheus Rodrigues; Bayer, Debora Missio; Conte, Luiza Chiarelli; Bertazzo , Luiz Antonio de Brito (Revista AIDIS de ingeniería y ciencias ambientales: Investigación, desarrollo y práctica, 2024)
Population care by water supply networks has evolved in the world but it is still not a reality for the entire population. In the existing systems, almost 40% of the volume of water available does not reach the user. An important variable that influences water losses in the system is the pressure. In this work, part of the water distribution system in the Brazilian city of So Gabriel, in the state of Rio Grande do Sul (RS), was evaluated through hydraulic simulation using [public domain, water distribution system modeling software package developed by the United States Environmental Protection Agencys (EPA) Water Supply and Water Resources Division] EPANET in three different scenarios: maximum, minimum and sustainable water consumption. In the simulations, the pressures and speeds in the distribution system were analyzed, which allowed the proposition of interventions such as: installation of accessories (pump and pressure reducing valves), reducing diameters of some pipe sections, alteration of the operating regime of already existing pumps, system sectorization and estimates of loss reduction resulting from these interventions.